A three dimensional micropatterned tumor model for breast cancer cell migration studies. (March 2016) - Peela, Nitish; Sam, Feba S.; Christenson, Wayne; Truong, Danh; Watson, Adam W.; Mouneimne, Ghassan; Ros, Robert; Nikkhah, Mehdi
Abstract: Breast cancer cell invasion is a highly orchestrated process driven by a myriad of complex microenvironmental stimuli, making it difficult to isolate and assess the effects of biochemical or biophysical cues (i.e. tumor architecture, matrix stiffness) on disease progression. In this regard, physiologically relevant tumor models are becoming instrumental to perform studies of cancer cell invasion within well-controlled conditions. Herein, we explored the use of photocrosslinkable hydrogels and a novel, two-step photolithography technique to microengineer a 3D breast tumor model. The microfabrication process enabled precise localization of cell-encapsulated circular constructs adjacent to a low stiffness matrix. To validate the model, breast cancer cell lines (MDA-MB-231, MCF7) and non-tumorigenic mammary epithelial cells (MCF10A) were embedded separately within the tumor model, all of which maintained high viability throughout the experiments. MDA-MB-231 cells exhibited extensive migratory behavior and invaded the surrounding matrix, whereas MCF7 or MCF10A cells formed clusters that stayed confined within the circular tumor regions. Additionally, real-time cell tracking indicated that the speed and persistence of MDA-MB-231 cells were substantially higher within the surrounding matrix compared to the circular constructs. Z-stack imaging of F-actin/α-tubulin cytoskeletal organization revealed unique 3D protrusions in MDA-MB-231 cells and an abundance of 3D clusters formed by MCF7 and MCF10A cells. Our results indicate that gelatin methacrylate (GelMA) hydrogel, integrated with the two-step photolithography technique, has great promise in the development of 3D tumor models with well-defined architecture and tunable stiffness.